Circulating Interleukin-7 in Human Pulmonary Arterial Hypertension - Diekmann, Franziska; Legchenko, Ekaterina; Chouvarine, Philippe; Lichtinghagen, Ralf; Bertram, Harald; Happel, Christoph M.; Hansmann, Georg (Frontiers in Cardiovascular Medicine, 2021)
Objectives. Emerging evidence suggests that natural killer (NK) cells and regulatory T cells (Tregs, CD4+) play protective immune-modulatory roles in pulmonary arterial hypertension (PAH) and associated right ventricular dysfunction (RVD). Interleukin-7 (IL-7) forms a heterodimer with HGF and secures B cell maturation, T and NK cell survival, and homeostasis. However, the role and potential impact of IL-7 on the pathobiology and severity of PAH is unknown. Methods. We recruited 10 pediatric patients with moderate PH (age range 3.9-18.5 years) and 10 non-PH controls (age range 2.0-17.3 years). EDTA blood was collected during cardiac catheterization from the superior vena cava (SVC), pulmonary artery (PA) and ascending aorta (AAO). Compartment-specific plasma concentrations of IL-7, VEGF-C, aldosterone, ICAM-1 and VCAM-1 were determined using Meso Scale Discovery’s multi array technology and the LIAISON Aldosterone Assay. Results. Children with PH had approximately 50% lower IL-7 concentrations (SVC: 6.61±1.04 vs. 13.25±1.10 pg/mL; p<0.001) and 59% lower VEGF-C plasma levels (p<0.001) in the SVC, PA and AAO vs. non-PH controls. Both IL-7 and VEGF-C plasma concentrations correlated negatively with the pulmonary vascular resistance (PVR)/systemic vascular resistance (SVR) ratio. Transpulmonary gradient analysis revealed that most patients had a step down in ICAM-1 and VCAM-1 plasma concentrations across the pulmonary circulation. Conclusion. This manuscript is the first report on decreased circulating IL-7 and VEGF-C concentrations in human PAH and their inverse correlations with invasive surrogates of PAH severity. Additional and larger studies are needed to explore the role of the immune-modulatory IL-7 and VEGF-C in pediatric and adult PAH.